Sulfonated inhibitors of the RNA editing ligases validate the essential role of the MRP1/2 proteins in kinetoplastid RNA editing - Mehta, Vaibhav; Moshiri, Houtan; Srikanth, Akshaya; Kala, Smriti; Lukeš, Julius; Salavati, Reza (RNA, 2020)
The RNA editing core complex (RECC) catalyzes mitochondrial U-insertion/deletion mRNA editing in trypanosomatid flagellates. Some naphthalene-based sulfonated compounds, such as C35 and MrB, competitively inhibit the auto-adenylylation activity of an essential RECC enzyme, kinetoplastid RNA editing ligase 1 (KREL1), required for the final step in editing. Previous studies revealed the ability of these compounds to interfere with the interaction between the editosome and its RNA substrates, consequently affecting all catalytic activities that comprise RNA editing. This observation implicates a critical function for the affected RNA binding proteins in RNA editing. In this study, using the inhibitory compounds, we analyzed the composition and editing activities of functional editosomes and identified the mitochondrial RNA binding proteins 1 and 2 (MRP1/2) as their preferred targets. While the MRP1/2 heterotetramer complex is known to bind guide RNA and promote annealing to its cognate pre-edited mRNA, its role in RNA editing remained enigmatic. We show that the compounds affect the association between the RECC and MRP1/2 heterotetramer. Furthermore, RECC purified post-treatment with these compounds exhibit compromised in vitro RNA editing activity that, remarkably, recovers upon the addition of recombinant MRP1/2 proteins. This work provides experimental evidence that the MRP1/2 heterotetramer is required for in vitro RNA editing activity and substantiates the hypothesized role of these proteins in presenting the RNA duplex to the catalytic complex in the initial steps of RNA editing.
Keywords: RNA, Guide, Kinetoplastida; RNA, Messenger; Mitochondria; RNA Editing; Recombinant Proteins; RNA, Mitochondrial; ligasy; Ligases; RNA mitochondriální; protozoální proteiny; mitochondriální proteiny; Trypanosoma brucei brucei; RNA, Protozoan; Mitochondrial Proteins; rekombinantní proteiny; RNA-Binding Proteins; editace RNA; RNA protozoální; guide RNA, Kinetoplastida; Protozoan Proteins; messenger RNA; mitochondrie; proteiny vázající RNA